2023
DOI: 10.1038/s41467-023-38627-x
|View full text |Cite
|
Sign up to set email alerts
|

MoS2 nanopore identifies single amino acids with sub-1 Dalton resolution

Abstract: The sequencing of single protein molecules using nanopores is faced with a huge challenge due to the lack of resolution needed to resolve single amino acids. Here we report the direct experimental identification of single amino acids in nanopores. With atomically engineered regions of sensitivity comparable to the size of single amino acids, MoS2 nanopores provide a sub-1 Dalton resolution for discriminating the chemical group difference of single amino acids, including recognizing the amino acid isomers. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…of proteins, or profiling protein conformations . For protein sequencing, many simulations and computational assessments with solid-state nanopores have been explored. The use of subnanometer solid-state pores to detect AAs in proteins at high speed and throughput is intriguing. , The low capacitance of these pores allows for rapid detection, and semiconductor manufacturing enables high throughput. High voltage is crucial for precise control over peptide translocation and to minimize diffusion and backstepping, albeit at the cost of decreasing the analyte dwell time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…of proteins, or profiling protein conformations . For protein sequencing, many simulations and computational assessments with solid-state nanopores have been explored. The use of subnanometer solid-state pores to detect AAs in proteins at high speed and throughput is intriguing. , The low capacitance of these pores allows for rapid detection, and semiconductor manufacturing enables high throughput. High voltage is crucial for precise control over peptide translocation and to minimize diffusion and backstepping, albeit at the cost of decreasing the analyte dwell time.…”
Section: Introductionmentioning
confidence: 99%
“…High voltage is crucial for precise control over peptide translocation and to minimize diffusion and backstepping, albeit at the cost of decreasing the analyte dwell time. Recently, Feng et al reported the direct experimental identification of 16 natural AAs by using MoS 2 nanopores, which can provide a sub-1 Da resolution . Despite the potential benefits, in terms of genome and proteome sequencing, the large sizes of solid-state pores are not particularly beneficial, as sequencing requires a narrow band of smaller pores (i.e., diameters <3 nm), with a degree of precision challenging for even the most advanced semiconductor manufacturing techniques that can achieve 2 nm line-rules. , Additionally, current solid-state pores lack scalable manufacturing processes and sufficient surface wetting control.…”
Section: Introductionmentioning
confidence: 99%
“…4 These rapid advances have motivated attempts to realize nanopore sequencing of peptides in a similar manner. 12−14 In the past few years, there has been a concerted effort to improve the spatial resolution, 15,16 where innovations are necessary to generate and capture distinctively featured current signals for all of the 20 different AAs constructing a given protein. 17,18 Biological nanopores are promising for identifying single AAs due to their nanoconfined spaces and customizable sensing interfaces, 19 which enable high spatiotemporal resolution and ultimate sensitivity for proteome analysis.…”
mentioning
confidence: 99%
“…De novo protein sequencing is crucial for understanding the diverse functions of proteins resulting from their highly variable amino acid (AA) sequences in all living systems. Compared to traditional methods like Edman degradation and mass spectrometry, which require a larger amount of protein and have limited sensitivity, , the nanopore technology presents a promising alternative. Nanopore-based analytical techniques allow for high-throughput single-molecule observation and direct identification of analytes via ionic or transverse tunneling current measurements. Over the past decade, nanopore sequencing of deoxyribonucleic acid (DNA) and ribonucleic acid (RNA) has become a mainstay of biomedical research and has led to substantial improvements in accuracy, read length, and throughput . These rapid advances have motivated attempts to realize nanopore sequencing of peptides in a similar manner. In the past few years, there has been a concerted effort to improve the spatial resolution, , where innovations are necessary to generate and capture distinctively featured current signals for all of the 20 different AAs constructing a given protein. , …”
mentioning
confidence: 99%
“…In analogy with genomics and proteomics sensing, nanopore technology stands as a promising label-free and single-molecule detection platform. It showcases an excellent capability to unveil crucial information, such as the shape, surface charge, and dynamic process of small molecules in situ .…”
mentioning
confidence: 99%